Mucosal Serotonin Reuptake Transporter Gene Expression and Serum Level among Iraqi Patients with Irritable Bowel Syndrome - Mohammed Abdullah Jebor; Ahmed Hashim Abbas Al-Janabi; Zahraa Abdali Althabet (Medical Journal of Babylon)
Background: A serotonin reuptake transporter is a protein that regulates serotonin levels in the body. Altered expression of the serotonin transporter gene and changes in serum levels of serotonin have been linked to irritable bowel syndrome (IBS). Research suggests that differences in serotonin transporter expression and serum levels may be associated with the development of IBS and its symptoms. Objective: This study aimed to measure selective serotonin reuptake transporter (SERT) expression level and SERT serum concentration among patients and control and find out the relationship between the severity of IBS syndrome and those levels. Materials and Methods: The present study included 100 specimens divided into two groups: 50 healthy control subjects and 50 IBS patients. Each patient and control had provided 2 mL of venous blood for the measurements of SERT level with serum, while 27 biopsy samples of patients and 16 mucosal samples of control were collected from patients with IBS. In this study, we used real-time polymerase chain reaction to quantify gene transcripts of SERT. Additionally, the SERT serum level was measured using enzyme-linked immunosorbent assay. These molecular analyses provide insights into the roles and interactions of these molecules, offering a better understanding of their functions in the biological system under investigation. Results: Data regarding serotonin expression was found to be nonnormally distributed; accordingly, they were expressed as median and rand (beside mean ± SD) and analyzed with a nonparametric Mann–Whitney U test. The relative median expression of the serotonin transporter gene was 1.05 folds (range 0.12–200 folds) in patients compared to 0.5 folds (range 0.07–12.43 folds) in control with no significant difference. The median serum level of the serotonin transporter in IBS patients was 12.8 pg/mL (range 0.6–36.13 pg/mL) with a mean lower than that of controls (median = 11.89 pg/mL, range = 9.44–33.5 pg/mL) with no significant difference. Conclusion: According to the findings of the current study, high SERT gene expression, as well as its serum level, is related to visceral hypersensitivity that leads to worsened development of IBS symptoms.